Forced marriage: What do professionals know?. (December 2021) - Villacampa, Carolina; Torres, Núria
Abstract: The adoption of a victim-centered approach to forced marriage requires implementing measures beyond prosecution oriented at preventing it and protecting its victims. To this end, professionals need to be able to identify its victims and recognize its effects on them. This paper aims to assess professionals' knowledge of the phenomenon, its dynamics, and its effects by presenting the findings of a qualitative research study conducted with 34 individuals in Spain. The results show that victim service providers have a broader understanding of forced marriage than criminal justice system professionals. They also indicate that the negative effects on victims vary depending on whether they submit to the forced marriage or escape from it. The study concludes with a discussion of the need to train professionals to recognize the various forms this reality may take and proposes that family-led cases be dealt with differently from those involving the sale of young women. Highlights: Victim service providers have a broader understanding of FM than CJS professionals. Criminal justice professionals identify forced marriages with human trafficking. Negative effects on victims vary depending on whether they submit or escape from it. Professional training to recognize all forms of forced marriage is needed. Family-led and human trafficking cases should be dealt with differently.